Impact of Cement Kiln Dust on Soil Geotechnical Properties - Rozhgar A. Hasan; Fahmy O. Mohammed; Nihad B. Salih (ARO-The Scientific Journal of Koya University)
As cement demand rises daily; kiln dust from cement-producing facilities is being collected in large quantities. This tiny dust poses a risk to the environment when it is disposed of. This study investigates the potential reuse of CKD as a stabilizing agent for expansive soils. The amount of CKD added to intact soil was 0%, 10%, 20%, 30%, and 40% of the dry mass of the soil. The liquid limit (LL) of the intact soil decreased after adding CKD from 47.7% to 43.7%, and the plastic limit (PL) from 26.97% decreased to 21.36%. A sharp decrease was observed in the consistency index (Ic) and toughness index (It), while the flow index (If), liquidity index (Li) and shrinkage index (Is) are noticeably increased. The unconfined compressive strength (qu), modulus of elasticity (E), and Resilient Modulus (Ur) increased for the samples cured for 7 days and 28 days; the rate of increase in the values of these parameters was observed to be higher in 28 days during the period compared to 7 days. Also, the shear strength and cohesion sharply increased after the soil was treated with CKD. The UPV also increased for both sets of prepared cylindrical soil samples. The CKD additives decreased the hydraulic conductivity of the soil and successfully improved the geotechnical characteristics of fine-grained soil. Thus, CKD can be repurposed as a sustainable soil stabilizer for slopes, subgrades, and foundations, providing a viable solution for its disposal and reducing environmental impact.